Associations between microorganism and maize plant to remedy mercury-contaminated soil - Lavezzo, Letícia Fernanda [UNESP] (2020)
Mercury (Hg) is one of the most toxic metals and is not essential for any organism. In this study, the potential of maize plants in association with bacteria to treat oxisol contaminated with Hg (II) was evaluated. The experiment was conducted in a controlled environment, and pots with 2 kg of oxisol were contaminated with HgCl2 solution at a dose of 36 mg kg-1 of Hg in a 7x4 factorial scheme: control (soil without Hg(II) and microorganisms), T2= (soil with Hg(II) and without microorganisms), and T3= soil with Hg(II) + Enterobacter cloacae, T4= Hg(II) + Bacillus subtilis, T5= Hg(II) + Enterobacter sp., T6= Hg(II) + Staphylococcus epidermidis, and T7= Hg(II) + Bacillus sp. Total Hg quantification was performed by atomic absorption spectrophotometry. At the end of the experiment, the soil pH was significantly lower (0.3 to 0.4 pH unit) in the T2 (no inoculation), Enterobacter cloacae, Enterobacter sp. and Bacillus sp. treatments. Neither contamination of soil with Hg nor plant associations with bacteria led to differences in the root dry mass of maize plants. Maize plants associated with Staphylococcus epidermidis and Bacillus sp. bacteria had lower shoot biomass (71 and 50%) compared to the treatment 2. The best remedial effect was observed with the association of maize plants with Bacillus sp., which recovered 19.67% of Hg(II) in the soil when compared to control and treatment 2 and treatment with B. subtilis. The recommendation is the use of B. subtilis to decrease the toxicity caused by Hg(II).